Intra-Cavitary Contrast-Enhanced Ultrasound: A Novel Radiation-Free Method for Detecting Abscess-Associated Penetrating Disease in Crohn's Disease. (13th December 2018) - Mao, Ren; Chen, Yu-Jun; Chen, Bai-Li; Xie, Xiao-Hua; He, Yao; Chen, Shu-ling; Xu, Ming; Li, Xue-Hua; Zhang, Jian; Song, Xin-Ming; Zeng, Zhi-Rong; Rimola, Jordi; et al.
Abstract: Background and Aim: Penetrating disease is a common condition complicating Crohn's disease [CD]. Establishing the presence of a fistula and the anatomical definition of the fistulous tracts are essential for deciding on appropriate treatment strategies. We aimed to assess the diagnostic accuracy of intra-cavitary contrast-enhanced ultrasound [IC-CEUS] for the detection of a fistulous tract associated with abscesses in CD patients. Methods: In this prospective cohort study, consecutive CD patients suspected of having an intra-abdominal abscess, who were referred for US-guided aspiration were recruited. IC-CEUS was performed by injecting diluted contrast agent [SonoVue] into the abscess cavity immediately following the ultrasound-guided needle abscess aspiration and drainage. The diagnostic accuracy of IC-CEUS in demonstrating the presence of fistulous tracts was compared with that of computed tomography enterography/magnetic resonance enterography [CTE/MRE], using surgical and gross pathological findings as the reference standard. Results: Thirty-one patients who underwent IC-CEUS and subsequent surgery were included in the final analysis. IC-CEUS demonstrated fistulous/sinus tracts in 26 of 31 participants with a sensitivity and specificity of 86.7 % (95% confidence interval [CI], 68.4–95.6%) and 100% [95% CI, 5.5–100.0%], respectively. Moreover, IC-CEUS correctly demonstrated fistulous/sinus tracts in 13 participants without delineation of fistulous/sinus tracts on CTE/MRE. Combining IC-CEUS and CTE/MRE, the fistula/sinus tract was clearly demonstrated in 29 patients [93.5%, 29/31]. The mean duration of the IC-CEUS procedure was 8.6 min [range 5.0–12.0]. No severe adverse events occurred during the IC-CEUS procedure. Conclusion: In this pilot study, IC-CEUS accurately delineated the anatomical definition of fistulous/sinus tracts associated with intra-abdominal abscesses in CD patients. As a radiation-free and safe technique, IC-CEUS may be used as an alternative/adjunctive method to CTE/MRE for detecting penetrating disease in patients with CD.